Digital Payment Capability, Trust, and Sales Growth among Philipphines Micro‑Retailers: The Moderating Role of Financial Literacy - Randy A. Cruz Randy A. Cruz (Kalam Practica Media, 2025)
Digital payments have become a defining feature of retail transformation across Southeast Asia, yet performance benefits from QR and e‑wallet diffusion remain uneven among micro‑retailers who operate with thin margins, limited buffers, and highly variable customer flows. This study examines how digital payment capability influences micro‑retailer sales growth through two behavioral mechanisms—customer trust and transaction convenience—while assessing whether financial literacy strengthens the conversion of capability into these demand‑side effects. Grounded in capability theory and technology‑trust perspectives, the model treats adoption as a minimum condition and focuses instead on execution maturity (reliability, exception handling, reconciliation, and communication competence). Survey data were collected from 436 Philipphines micro‑retailers across three provinces with diverse infrastructure conditions. Partial Least Squares Structural Equation Modeling (PLS‑SEM) was applied to evaluate direct effects, parallel mediation, and moderation. Results show that digital payment capability relates positively to sales growth, with trust and convenience operating as partial mediators; financial literacy strengthens the capability‑to‑trust and capability‑to‑convenience pathways. The findings indicate that cashless ecosystems deliver inclusive performance gains when merchant‑side capability is supported by practical literacy and governance routines that stabilize customer experience. Policy implications emphasize pairing QR expansion with merchant education, simplified reconciliation tools, and dispute‑resolution reliability rather than relying on infrastructure rollout alone.